When Portugal is too small to build case study: Mota-Engil - Martins, Diogo Lourenço (2019)
The construction sector has a key role in any country’s economy. The distinctiveness of this industry is related to its complexity, to its range of possible inputs and outputs, the long value-chain, the development of externalities, and by the construction investment multiplicative effect on economy, particularly in the employment. On the other hand, it is a sector intrinsically dependent on the economy business cycles, particularly to public expenditure and credit access and the evolution of interest rates. The financial crisis had a tremendous negative impact in the Portuguese construction, motivating/forcing the major Portuguese contractors to endeavor to the internationalization solution. These firms had different motivations, generally seeking out to achieve growth levels that were not possible if they stayed in a Portugal that seems to be getting smaller to the contractor’s ambitions to build, and doing so, in a context that the construction/engineering industry in Portugal starts to show signs of recovery after the recession, and the major contractors are reporting around 80% revenue overseas. In this context, the subject of internationalization in the industry of construction gains especial interest to understand the cases of success. The success case in study will be the Mota-Engil Group, by far the Portuguese leader and best performing company, the only construction and engineering company in the PSI20 - the main Portuguese Stock Index - in 2017, reporting a turnover of 2,597 million Euros and a backlog that reached €5,138 Mn, of which 79% outside Europe. Present in the 51st position on ENR’s 2018 Top 250 International Contractors, after ranking 58th in 2017. In the year of 2018 the company entered in 4 new markets extending their presence to more than 30 countries.